Rationale and Design of a Randomized, Open‐Label, Parallel‐Group Study of Esaxerenone Versus Angiotensin Receptor Blockers in Older Patients With Uncontrolled Hypertension on Calcium Channel Blocker Monotherapy (ESCORT‐HT) - Kazuomi Kario; Tomohiro Katsuya; Tatsuo Shimosawa; Takashi Taguchi; Ayumi Tanabe; Mitsuru Ohishi; the ESCORT‐HT investigators (The Journal of Clinical Hypertension)
ABSTRACT Angiotensin II receptor blockers (ARBs) and calcium channel blockers (CCBs) are commonly prescribed as first‐ and second‐line treatments for older Japanese patients with hypertension. However, due to age‐related decline in renin activity, the effectiveness of ARBs may decrease. This highlights the need for other antihypertensive agents to be used in combination with CCBs to replace ARBs for more effective blood pressure (BP) control. The ESCORT‐HT study is a multicenter, randomized, controlled, open‐label, parallel‐group study with a 4‐week run‐in period and 12‐week treatment period. This study aims to evaluate the efficacy of esaxerenone as a second‐line treatment for hypertension and to determine whether its BP‐lowering effect is noninferior to that of ARBs in older patients with uncontrolled hypertension on CCB monotherapy. The safety profiles of esaxerenone and ARBs will also be evaluated. Patients will be randomly assigned in a 1:1 ratio to receive either esaxerenone or an ARB. The primary efficacy endpoint will be the change from baseline in morning home systolic BP at the end of the treatment period. The BP‐lowering effect of esaxerenone will be considered noninferior to that of ARBs if the upper limit of the two‐sided 95% confidence interval (CI) for the difference in systolic BP change between esaxerenone and ARB is <3.8 mmHg, and will be considered superior if the upper limit of the two‐sided 95% CI is <0. The findings may elucidate the possible benefits of earlier use of mineralocorticoid receptor blockers in combination with CCBs in older patients with essential hypertension.